Temporal Dynamics of MOG Antibodies in Children With Acquired Demyelinating Syndrome. Issue 6 (13th November 2022) - Wendel, Eva Maria; Thonke, Helen Sophie; Bertolini, Annikki; Baumann, Matthias; Blaschek, Astrid; Merkenschlager, Andreas; Karenfort, Michael; Kornek, Barbara; Lechner, Christian; Pohl, Daniela; Pritsch, Martin; Schanda, Kathrin; et al.
Abstract : Background and Objective: The spectrum of myelin oligodendrocyte glycoprotein (MOG) antibody–associated disorder (MOGAD) comprises monophasic diseases such as acute disseminated encephalomyelitis (ADEM), optic neuritis (ON), and transverse myelitis and relapsing courses of these presentations. Persistently high MOG antibodies (MOG immunoglobulin G [IgG]) are found in patients with a relapsing disease course. Prognostic factors to determine the clinical course of children with a first MOGAD are still lacking. The objective of the study is to assess the clinical and laboratory prognostic parameters for a risk of relapse and the temporal dynamics of MOG‐IgG titers in children with MOGAD in correlation with clinical presentation and disease course. Methods: In this prospective multicenter hospital-based study, children with a first demyelinating attack and complete data set comprising clinical and radiologic findings, MOG-IgG titer at onset, and clinical and serologic follow-up data were included. Serum samples were analyzed by live cell-based assay, and a titer level of ≥1:160 was classified as MOG-IgG–positive. Results: One hundred sixteen children (f:m = 57:59) with MOGAD were included and initially diagnosed with ADEM (n = 59), unilateral ON (n = 12), bilateral ON (n = 16), myelitis (n = 6), neuromyelitis optica spectrum disorder (n = 8) or encephalitis (n = 6). The median follow-up time was 3 years in monophasic and 5 years in relapsing patients. There was no significant association between disease course and MOG-IgG titers at onset, sex, age at presentation, or clinical phenotype. Seroconversion to MOG-IgG–negative within 2 years of the initial event showed a significant risk reduction for a relapsing disease course. Forty-two/one hundred sixteen patients (monophasic n = 26, relapsing n = 16) had serial MOG-IgG testing in years 1 and 2 after the initial event. In contrast to relapsing patients, monophasic patients showed a significant decrease of MOG-IgG titers during the first and second years, often with seroconversion to negative titers. During the follow-up, MOG-IgG titers were persistently higher in relapsing than in monophasic patients. Decrease in MOG-IgG of ≥3 dilution steps after the first and second years was shown to be associated with a decreased risk of relapses. In our cohort, no patient experienced a relapse after seroconversion to MOG-IgG–negative. Discussion: In this study, patients with declining MOG-IgG titers, particularly those with seroconversion to MOG-IgG–negative, are shown to have a significantly reduced relapse risk.